Death, desire and loss in western culture - Dollimore, Jonathan (Routledge, 2001)
Death, Desire and Loss in Western Culture is a rich testament to our ubiquitous preoccupation with the tangled web of death and desire. In these pages we find nuanced analysis that blends Plato with Shelley, Hölderlin with Foucault. Dollimore, a gifted thinker, is not content to summarize these texts from afar; instead, he weaves a thread through each to tell the magnificent story of the making of the modern individual.